HEART FAILURE WITH PRESERVED EJECTION FRACTION: FROM PROGNOSIS TO CARDIAC EFFECTS. THE ROLE OF FITNESS, PHYSICAL ACTIVITY AND EXERCISE TRAINING. - Cristine Schmidt (2018)
Rational: Heart failure with preserved ejection fraction (HFpEF) continues to be refractory to available therapies, with current treatment guidelines highlighting the importance of focusing on the improvement of patient's well-being or other healthrelated outcomes. There is also an increasing awareness of the need for novel approaches not only for the treatment of HFpEF but also for its prevention through the early identification and management of potential modifiable contributing risk factors. Physical fitness or physical activity (PA) are becoming recognized as key modifiable factors for the prevention of HFpEF and management of cardinal symptoms such as exercise intolerance and quality of life (QoL). From a clinical perspective, physical fitness and PA may be considered important targets if we aim to maximize the health care of these patients. However, there are some gaps in this field that may challenge the effectiveness of physical fitness and PA basedinterventions. First, because physical fitness is a multicomponent construct, it is important to understand how this syndrome affects the different components, and which of them is better representative of health-related outcomes. Second, in order to provide tailored counselling and prescription to HFpEF patients, it is crucial that the instruments that we use to measure PA levels are accurate and reliable. While the use of questionnaires may be easy to apply in the clinical practice, it remains to be confirmed if self-reported and objectively measured PA is correlated in HFpEF. Third, while there is some evidence that exercise training can improve diastolic function in HFpEF patients, the mechanisms underlying these changes remain poorly comprehend. Purpose: In the current work, we propose to: i) study the association between different components of physical fitness and the dimensions of QoL in HFpEF patients; ii) examine which of the physical fitness components are independently related to different dimensions of QoL; iii) to determine the validity of the International Physical Activity Questionnaire (IPAQ) against objective measures from accelerometry in HFpEF patients; iv) to describe the patterns of daily PA and sedentary time and assess which is better associated with prognostic indicators; v) evaluate the effects of exercise training on LV function and structure, and underlying molecular changes, using the ZFF1 obese animal model of HFpEF. Methods: In order to accomplish the proposed aims, we evaluated 24 HFpEF patients (Study I and II). Patients were assessed for physical fitness [dynamic balance and mobility (8-feet-up-and go test), upper body strength (handgrip strength), cardiorespiratory fitness (CRF) (6-minute-walking test), body composition (body mass index)] and for QoL (Minnesota Living With Heart Failure Questionnaire). Physical activity was assessed through the IPAQ short version and triaxial accelerometry (ActiGraph GTX3). In order to evaluate the effects of exercise training on LV function and structure, and underlying molecular changes (Study III), we used the ZSF1 obese animal model. Animals were randomly divided in a training or sedentary group. At the end of the protocol, all animals were submitted to exercise tolerance test, and invasive hemodynamic evaluation. After sacrifice, blood and left ventricular samples were collected for analysis. XXIV Results: In Study I, our data suggests that dynamic balance and mobility is the only physical fitness component that better capture QoL in HFpEF patients. In Study II, our data suggests that the IPAQ short version underestimates sedentary time and over-estimates MVPA. In addition, patients spent only a minority of their time involved in moderate-to-vigorous PA, which was the only PA pattern positively associated with prognostic indicators. Finally, in Study III, we show that chronic exercise training improved exercise capacity, attenuated LV stiffness and reduced circulating levels of inflammatory cytokines and markers of endothelial dysfunction and oxidative stress in rats with HFpEF. Conclusions: Our data suggests that physical fitness, particularly dynamic balance and mobility, should be evaluated in HFpEF patients, once that it is associated with QoL. Also, physical activity data gathered solely by self-reported instruments may lead biased counselling and prescription. Regarding to PA patterns, our data points for the importance of recommending HFpEF to more engaged in MVPA. Finally, exercise training seems to positively impact left ventricular stiffness by modulating both cardiomyocyte's intrinsic proprieties and extracellular matrix remodelling.